Working mothers self care practices as a coping mechanism: An interpretative phenomenological analysis - Mahadeo-Diercks, Sarika (Graduate School of Business (GSB), 2024)
Title: Experiences of modern-day motherhood and work: An interpretative phenomenological study of professional working mothers' self-care and coping Objective: This study explores the experiences and understandings of self-care and coping in professional working women in South Africa who are first-time mothers. Working mothers find it difficult to balance work and home responsibilities, and often at the expense of self-care. Method: The sample comprised five mothers of singletons working in business or the corporate sector, who had integrated back into work for at least six months after maternity leave. They began by drawing a picture of how they saw themselves coping with the demands of being a professional working mother. Their portrayal provided a strong introduction to the conversation about their experiences of self-care and coping post-motherhood. Data was collected using semi-structured interviews. The interviews were analysed using interpretative phenomenological analysis. Results: The participants descriptions highlighted the challenges of meeting the demands of being a working professional and a first-time mother. The participants' accounts offered deep insights into their experiences of motherhood, self-care and coping. This study suggests that participants found the experience of motherhood a transition that they were not fully prepared for, regarding increased demands and unrealistic expectations. There was a strong sense of pressure on them to live up to the ideals of motherhood. Self-care was challenging particularly once they had returned to work in relation to time, energy, and support. Conclusion: Self-care was an enabler to coping and lack of self-care led to poor coping. Keywords: Professional working mothers, self-care, coping, interpretative phenomenological analysis (IPA)